(untitled) (GYMNASIUM, 2009)
This paper aims to identify key factors specific to the game of volleyball during the course of its generating information detrmină adapting the action of players. The determination of these sources of information and knowledge they generate information that can lead even fomarea habits to discover key issues that characterize a game situation. Such actions may be adjusted in game more effectively.